Degradation of diesel and phenol using bacteria isolated from petroleum hydrocarbon contaminated soil - Ahmed, F; Fakhruddin, ANM; Kabir, MM (Bangladesh Journal of Scientific and Industrial Research, 2018)
In the present investigation, diesel degrading bacteria were isolated from petroleum hydrocarbon contaminated soil and evaluated their degradation potentials of diesel and phenol at various concentrations. Total hydrocarbon was identified by extracting mixed standard sample (MSS) method from the contaminated soil and scanning wavelength from 190 to 280 nm by means of UV-visible spectrophotometer. The absorption peak of MSS solution dissolved in hexane was stable at 215 nm to 230 nm. The average number of diesel degrading bacteria in the soil sample was 2.52 × 103 at 32 ºC for72 hours. One of the representative isolates was used to degrade diesel at varying amount. At 24 h of incubation, bacterial growth increased up in 20% (v/v) of diesel but in 25% (v/v) of diesel bacterial growth decreased. This isolate completely degraded 50 mg/L phenol after 96 h of incubation from the culture medium. The isolated bacteria can be used as an effective candidate for bioremediation of diesel and phenol from the hydrocarbon contaminated environments. Bangladesh J. Sci. Ind. Res.53(1), 53-62, 2018